Other voices: authors' literary-academic presence and publication in the discursive world system. Issue 4 (4th July 2018) - Larson, Jay
ABSTRACT: Academic publication is an international phenomenon, annually involving thousands of scholars, publishers, and institutions worldwide. Despite global authorship, influential publications operate primarily zones of geopolitical and economic power in North America and Western Europe. The primary objective of this paper is to examine the effects of dominant publication practices on work produced by authors outside dominant regions. I also propose a world systems model extending beyond dynamics of material production to also encompass cultural epistemologies, resources, and language as elements of knowledge production. In a critical examination grounded in world systems theory, discourse analysis, and post-colonial studies, I delineate the manner in which practices affect a series of shifts in literary-academic presence – an author's textual expression of cultural, regional, linguistic, and scholarly orientation. I argue that conventions produced in global centers of intellectual influence lead authors to reposition their literary-academic presences in a series of geographic, rhetorical, and linguistic shifts.